Length-weight relationships and microhabitat effect on relative health condition of mangrove fishes from Chiapas, Mexico (UNED Research Journal, 2022)
Introduction: The specialized root systems of mangroves provide protection and food resources for young and small fish, and it is known that they are reflected on some health condition and growth characteristics of the fish, but much remains to be learned about this subject in the tropics. Objective: To estimate length-weight relationships for ten bony fish species in two tropical mangroves and to compare the allometry and health condition for three species shared among those mangroves. Methods: Between May and November 2019, we collected 1 500 fish specimens from the roots of two mangroves in Chiapas, Mexico (1 322 fishes in stilt-roots and 188 in pneumatophores). We estimated Length-Weight relations with W=aSLb, and the regression parameters (a and b) were calculated by least-squares; as well as univariate analyses to compare standard length, regression slopes, and relative condition among individuals of Poecilia nelsoni, Poeciliopsis fasciata and Dormitator latifrons. Results: The standard length for all species ranged between 0,7 and 21,5 cm and weight between 0,01 and 209,34 g; the regression b-values varied from 2,844 for P. fasciata and 3,847 for Poeciliopsis pleurospilus. TDetermination coefficients were >0,9 for eight species in stilt-roots and for three species in pneumatophores. Specimens of three species collected in both microhabitats were smaller in pneumatophores than in stilt-roots and also differed in b-values; however, the relative health condition was higher only in P. fasciata. Conclusion: The intrinsic conditions of stilt-roots and pneumatophores influence the average size and allometry of fishes at this site. The relative condition does not vary between microhabitats for most species, but may reflect development strategies associated with the environment.
Keywords: Ichthyofauna; mangroove roots; standard lenght; allometry coefficient; coefficient of determination